Experimental investigation of the behavioral effects of new phosphorylated thiosemicarbazides - A. V. Nikitina; I. I. Semina; D. O. Nikitin; E. L. Gavrilova; I. A. Krutov; A. O. Isaeva (Фармакокинетика и Фармакодинамика)
Relevance. It is known that the existing drug therapy for cognitive disorders is characterized by low rates of eﬃcacy and safety, as well as symptomatic orientation. Therefore, the search for new drugs in this area is an urgent issue, the solution of which can be phosphorylated derivatives of thiosemicarbazides (PTC), which have a multitarget mechanism of action.Aim. Study of acute toxicity and behavioral eﬀects of PTC in mice.Methods. The objects of study are 2 new compounds of the PTC series: 2-[2-(Diphenylphosphoryl)acetyl]hydrazinecarbothioamide (T7) and 2-[2-(Diphenylphosphoryl) acetyl]-N-phenylhydrazinecarbothioamide (T8). The reference drug is diphenylphosphorylacetic acid hydrazide (phosenazid). After determining the acute toxicity with a single intraperitoneal injection, the eﬀect of PTK on the behavior of mice was studied in the models "Open ﬁeld" (OP), "Elevated plus maze" (EPM), "Dark-light chamber" (DLC) and "Behavioral despair" (BD). For statistical analysis, the GraphPadPrism 8.0.1 program was used with the calculation of Student's t-test.Results. It has been established that new PTC are less toxic than fosenazid. Behavioral testing showed that i.m. administration of T8 in test "OP" contributed to an increase in exploratory (6 and 12 mg/kg) and motor (12 mg/kg) activity, the development of an anxiolytic eﬀect in the tests "EPM" (12 mg/kg) and "DLC" (6 mg / kg), and in "BD" (12 mg / kg) antidepressant eﬀect. With the intravenous administration of T7, an increase in motor activity in the “OP” (16 mg / kg) was noted.Conclusion. Compounds of a number of PTC are promising for further synthesis and development as potential drugs with a diﬀerent spectrum of psychotropic activitys.